The phenomenolgoical experience of posttraumatic growth in the context of a traumatic bereavement - Acheson, Kerry (Rhodes University, Faculty of Humanities, Department of Psychology, 2009)
The present study involves an exploration of the phenomenological expenence of posttraumatic growth in the context of a traumatic bereavement. An idiographic case study of a student who had witnessed her mother's death twelve years previously was conducted. Semi-structured interviews elicited data which was analysed using interpretative phenomenological analysis (IP A). Posttraumatic growth was found to have developed with regards to self-perception, relationships, and also in a broader spiritual and existential domain. The findings of this study shed light on the extant posttraumatic growth literature. In particular, findings were discussed in relation to the posttraumatic growth model as proposed by Calhoun and Tedeschi (2006). As posttraumatic growth is a relatively young concept, further research is needed in order to understand the meaning of reported growth more fully. While posttraumatic growth has been investigated in the context of bereavement, future research should distinguish more clearly between growth following traumatic and non-traumatic bereavement. Posttraumatic growth has received minimal empirical attention in South Africa, and therefore exploration of this area is suggested in the future.,KMBT_363,Adobe Acrobat 9.54 Paper Capture Plug-in
Keywords: Post-traumatic stress disorder -- Case studies; Bereavement -- Psychological aspects; Death -- Psychological aspects; Phenomenological psychology Grief